2014
DOI: 10.1111/hdi.12200
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and inflammatory/anti‐inflammatory cytokines in chronic kidney disease and end‐stage renal disease patients: A review of literature

Abstract: Depression is a common psychiatric disorder in patients with advanced chronic kidney diseases (CKDs). Strong correlation has been reported between depression and patients' morbidity and mortality among dialysis patients. On the contrary, chronic inflammation may be a major contributor to morbidity and mortality in these patients. Elevated plasma levels of proinflammatory cytokines, especially C-reactive protein and interleukin (IL)-6, have been correlated with cardiovascular events, hospitalization, and all-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 103 publications
(342 reference statements)
0
63
0
2
Order By: Relevance
“…3,54 This can lead to alterations in malnutrition, immunity, inflammation, and atherosclerosis states. 55 This theory was also supported by early evidence that depression could be involved in the development of malnutrition, inflammation, and atherosclerosis (MIA) in patients undergoing dialysis. 56 Second, depression might also be associated with clinical outcomes via behavioral pathways.…”
Section: Mechanism Linking Depression To Outcomesmentioning
confidence: 89%
“…3,54 This can lead to alterations in malnutrition, immunity, inflammation, and atherosclerosis states. 55 This theory was also supported by early evidence that depression could be involved in the development of malnutrition, inflammation, and atherosclerosis (MIA) in patients undergoing dialysis. 56 Second, depression might also be associated with clinical outcomes via behavioral pathways.…”
Section: Mechanism Linking Depression To Outcomesmentioning
confidence: 89%
“…Pro-inflammatory cytokines may directly cause anorexia via influence on the brain. In addition, inflammatory markers, particularly IL-6, may be associated with depression in CKD and ESRD, which by itself is a predictor of morbidity and mortality [24] and can cause decreased nutrient intake. However, inflammation may not only cause true malnutrition, but can also increase resting energy expenditure.…”
Section: Outcomes Of Inflammation In Ckdmentioning
confidence: 99%
“…Depression may result in adverse clinical outcomes by affecting compliance with dialysis and medication regimes, alteration of immune system function, and its detrimental effect on nutritional status . Depressed dialysis patients had significantly elevated plasma levels of pro‐inflammatory cytokines, in particular interleukin (IL)‐6, which may be associated with adverse cardiovascular outcomes . A recent randomized, double‐blind, placebo‐controlled trial showed that 12‐week treatment with sertraline significantly decreased serum IL‐6 levels in HD patients with depression .…”
Section: Introductionmentioning
confidence: 99%